2019
DOI: 10.1002/cssc.201903117
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 to CO by N,S Dual‐Doped Carbon Nanoweb Catalysts

Abstract: Converting CO2 into useful chemicals through an electrocatalytic process is an attractive solution to reduce CO2 in the atmosphere. However, the process suffers from high overpotential, low activity, or poor product selectivity. In this study, N,S dual‐doped carbon nanoweb (NSCNW) materials were proposed as an efficient nonmetallic electrocatalyst for CO2 reduction. The NSCNW catalysts preferentially and rapidly converted CO2 into CO with a high Faradaic efficiency of 93.4 % and a partial current density of −5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The introduction of heteroatoms breaks some initial C−C bonds and forms new carbon‐heteroatom bonds in the carbon matrix, resulting in the creation of defects and unique heteroatom sites, which have been considered as catalytically active sites for CO 2 RR. When doping the pristine carbon with two kinds of heteroatoms, synergistic effects on the reaction pathways are expected to tune the activity and selectivity of CO 2 RR [24–30] . For instance, nitrogen and sulfur co‐doped carbon hierarchically porous carbon nanofiber membranes can achieve a CO Faradaic efficiency of 94%, higher than the nitrogen‐doped reference sample.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of heteroatoms breaks some initial C−C bonds and forms new carbon‐heteroatom bonds in the carbon matrix, resulting in the creation of defects and unique heteroatom sites, which have been considered as catalytically active sites for CO 2 RR. When doping the pristine carbon with two kinds of heteroatoms, synergistic effects on the reaction pathways are expected to tune the activity and selectivity of CO 2 RR [24–30] . For instance, nitrogen and sulfur co‐doped carbon hierarchically porous carbon nanofiber membranes can achieve a CO Faradaic efficiency of 94%, higher than the nitrogen‐doped reference sample.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the N and S dual‐doping, the carbon nanoweb serves as an efficient nonmetallic electrocatalyst for conversion of CO 2 into CO with a FE of 93.4%. [ 148 ] On the contrary, Li et al. found that S, N‐doped carbon exhibit a catalytic performance toward electrochemical reduction of CO 2 into CH 4 with a FE of 0.18%.…”
Section: Electrocatalysts For the Reduction Of Co2 To Ch4mentioning
confidence: 99%
“…[147] Moreover, the catalytic activity of CO 2 RR by N-doped carbon materials highly relies on the amount and local electronic properties of N atoms in the carbon matrix, which determines the number of active sites and intrinsic catalytic nature, respectively. [148] Furthermore, among these N species in the carbon matrix, pyridinic N is the most active sites for CO 2 reduction followed by pyrrolic and graphitic N. [149] It is worth noting that Kumar et al proposed that it is the reduced/ positively charged carbon atoms rather than the electronegative nitrogen atoms responsible for the CO 2 reduction. [145] The positively charged quaternary N in the matrix are the sites for the stabilization of *CO 2…”
Section: Mnc Materials As Co 2 Rr Catalysts For Chmentioning
confidence: 99%
“…Though the intrinsic activity of carbon materials is poor, the introduction of heteroatoms (N, S, B, etc.) can effectively promote their electrochemical activity and selectivity [19][20][21][22][23]. Taking N-doped carbon materials as the examples, the doping N atoms exist in the forms of pyridinic N, pyrrolic N, graphitic N, and oxidized N in the carbon materials.…”
Section: Plasma-regulated N-doped Carbon Nanotube Arrays For Efficienmentioning
confidence: 99%